Assessment and improvement of the wave generation accuracy using a wave separation method. (15th April 2022) - Padilla, Enrique M.; Alsina, Jose M.
Abstract: Free-wave contamination is a non-desirable but frequent characteristic in many wave tank experiments. Higher-order wave generation is not widely implemented yet, whereas the effectiveness of active wave absorption systems is frequency-dependent, and usually unknown. The resulting free-wave contamination usually remains unnoticed, but may have important consequences especially at low frequencies. We present a Generation–Separation–Compensation (GSC) procedure to identify, quantify and attenuate the free-wave contamination. The resulting wave field behaves as expected from a higher-order wave generation with no re-reflections at the wave paddle. The attenuation ratio of the unwanted energy content is relatively high (between 60% to 90%). The GSC procedure uses the general framework for wave separation proposed by Padilla and Alsina (2020) with an array of in-line probes. The application of this technique over experimental data is presented with excellent results. The robustness of the qualitative analysis is guaranteed for experimental settings fulfilling a minimum distance between the first and the last probe and a maximum spacing between probes. The stability of the quantitative analysis is guaranteed when P, number of probes forming the array, is above five, and Δ x s e p / λ, ratio between the spacing of the probes forming the array and the wavelength, is within the recommended range 0.1–0.45. Highlights: Free-wave contamination is detected using the qualitative analysis of Padilla and Alsina (2020). The Generation–Separation–Compensation (GSC) procedure is to (1) identify and quantify and (2) attenuate, if needed, the existing free-wave contamination. The applicability over experimental data of the GSC procedure is discussed. The GSC procedure minimizes the free-wave contamination with satisfactory results, especially at the low frequencies.